2020
DOI: 10.1097/adm.0000000000000702
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Risk Factors for Testing of Hepatitis C in Non-Birth Cohort Patients: Is Universal Screening Necessary?

Abstract: Objectives: CDC reported that 45% of Hepatitis C (HCV) infected people denied known risk factors. Electronic health record RF-based, non-Birth Cohort (born outside of years 1945–1965) screening is challenging as risk factors are often input as nonsearchable data. Testing non-Birth Cohort patients solely based on risk factors has the potential to miss a substantial number of HCV infected patients. The aim was to determine the HCV antibody positive prevalence who would have been missed had providers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…However, seroconversion risk was 3.2-fold higher with long-term vs no long-term prescription opioid therapy and there was evidence of higher risk with more intense long-term use (chronic vs episodic) and at higher daily doses (≥90 vs <90 MEQ). Our findings support 2 recent case-control analyses identifying an association between medically dispensed prescription opioids and HCV diagnosis . One of these analyses found that older individuals (age >40 years) with a history of prescription opioid use were 11 times more likely to test positive on an HCV antibody test, and the other analysis found prior prescription opioid dispensation to be the second most important variable for predicting HCV diagnosis in a machine learning prediction model .…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…However, seroconversion risk was 3.2-fold higher with long-term vs no long-term prescription opioid therapy and there was evidence of higher risk with more intense long-term use (chronic vs episodic) and at higher daily doses (≥90 vs <90 MEQ). Our findings support 2 recent case-control analyses identifying an association between medically dispensed prescription opioids and HCV diagnosis . One of these analyses found that older individuals (age >40 years) with a history of prescription opioid use were 11 times more likely to test positive on an HCV antibody test, and the other analysis found prior prescription opioid dispensation to be the second most important variable for predicting HCV diagnosis in a machine learning prediction model .…”
Section: Discussionsupporting
confidence: 86%
“…42,43 In addition, owing to the inability to identify the exact date of seroconversion, some individuals who initiated prescription opioid therapy during follow-up may have done so after acquiring HCV; thus, prescription opioid therapy could be a proxy for HCV-related pain. 44 Our findings may support the offer of an HCV test to people with a history of long-term prescription opioid therapy 25,26,45 could increase the risk of harm and may facilitate illicit drug use in some individuals. 20,42 There is a need to support shared, patient-centered decision-making with regard to initiating, tapering, and discontinuing prescription opioid therapy.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations